Evaluating Efficacy and Safety of Combination Medication of Atorvastatin and a Herbal Formula Containing Salvia miltiorrhiza and Pueraria lobata on Hyperlipidemia. (25th August 2017) - Cheung, David Wing‐Shing; Koon, Chi‐Man; Wong, Pui‐Han; Yau, Ka‐Chun; Wat, Elaine; Hung, Angela Sze‐Man; Wang, Yan‐Ping; Lau, Kit‐Man; Ko, Chun‐Hay; Chan, Judy Yuet‐Wa; Waye, Mary Miu‐Yee; Fung, Kwok‐Pui
Abstract : Despite being a potent hypolipidemic drug, atorvastatin (AS) possesses certain adverse effects. Using AS and an herbal formula (Danshen and Gegen, DG) in combination may achieve potentiated hypolipidemic effects and also reduce its adverse effects. Hence, this study aimed to investigate the efficacy and safety of an AS and DG combination on high‐fat diet‐induced hyperlipidemia. Treatment outcomes were assessed by measuring parameters including body weight, adipose tissue, liver, total cholesterol, triglyceride, and low‐density and high‐density lipoprotein cholesterol. Measurements of adverse effects were achieved by determining aspartate aminotransferase (AST), alanine transaminase (ALT), and creatine kinase (CK). Danshen and Gegen, as well as AS alone, reduced body weight, adipose tissue, liver weight, liver fat vacuoles, total liver lipids, total cholesterol, triglyceride, low‐density lipoprotein cholesterol, and high‐density lipoprotein cholesterol in high‐fat diet‐fed mice but increased AST, ALT, and CK. A combination of AS and DG was able to enhance reduced effects on the aforementioned parameters in relation to hyperlipidemia over AS or DG alone. It also reduced the elevation of AST, ALT, and CK induced than by AS or DG alone. Results demonstrated that an AS and DG combination resulted in stronger hypolipidemic effects than with AS or DG alone. Additionally, DG might attenuate adverse effects of AS on the liver and skeletal muscle. Copyright © 2017 John Wiley & Sons, Ltd.